Employee Discipline Management: How to Pursue Disciplinary Actions Effectively and Legally in The Workplaces - Chai, Jaan Xin; Ismail, Fadillah; Khan, Muhammad Asad (Journal of Techno-Social, 2021)
Taking action against troubled employees is very important. The organization’s failure to act immediately indicates that negative behavior can be accepted or approved by management. If this situation occurs and persists, disciplinary action becomes more complicated and difficult. Problematic behavior requires an effective and accurate response from management by evaluating fairness as well as legally. This issue needs to be addressed wisely. so that the actions taken have a positive impact and motivate employees. Hence this study aims to how management should act in managing disciplinary problems in an effort to create workplace harmony.